2013
DOI: 10.17509/ijal.v2i2.164
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of English-Only Policy in the Tertiary Efl Context in Taiwan

Abstract: The implementation of English-only policy in the English classes at Wenzao Ursuline College of Languages in Taiwan has continued for nearly 40 years. Its advantages and disadvantages have also been debated and challenged because of the rising demands on students' English proficiency in Taiwan. This study intended to reexamine the efficiency of the implementation of English-only policy in the English learning at a college of languages in Taiwan. Both quantitative and qualitative methods were used in the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Empirical research has highlighted the practical benefits that the English-only practice brings about. Firstly, it was found that an English-only policy can make students improve their listening skills (Wei, 2013).…”
Section: English-only Instruction In L2/fl Teachingmentioning
confidence: 99%
“…Empirical research has highlighted the practical benefits that the English-only practice brings about. Firstly, it was found that an English-only policy can make students improve their listening skills (Wei, 2013).…”
Section: English-only Instruction In L2/fl Teachingmentioning
confidence: 99%
“…Furthermore, Sa'd and Qadermazi (2015) mentioned that one of the major advantages of avoiding L1 in the EFL classes is stated as being the improvement of speaking and listening skills, maximizing students' exposure to English and their becoming accustomed to it. It is supported by Wei (2013) who found the students' progress in English listening and speaking proficiency in the basic and lower-intermediate levels due to the English-only policy.…”
Section: Speaking To the Students And Handling Their Responsesmentioning
confidence: 87%
“…Auerbach (1993) argues that English-only instruction in ESL countries has been regarded as "a 'natural' and 'common sense practice' which is rooted in a particular ideological perspective that serves to reinforce inequities in the broader social order" Arab World English Journal www.awej.org ISSN: 2229-9327 26 ( p.9). Many researchers (Auerbach, 1993;Cummins, 1986;Huang, 2009;Lee, 2010;Lotherington, 1996;Lucas & Katz, 1994;Morrison & Lui, 2000;Phillipson, 1992;Wei, 2013;Wiley & Lukes, 1996) argue that a monolingual approach to teaching English is ideological. However, in reality English-only immersion teaching is the most popular teaching method for children in English language schools in Taiwan (Chang, 2004).…”
Section: English-only Immersion Methodsmentioning
confidence: 99%